Facile and sensitive electrochemical detection of methyl parathion based on a sensing platform constructed by the direct growth of carbon nanotubes on carbon paper. Issue 63 (21st June 2016) - Yue, Xiaoyue; Han, Pengxian; Zhu, Wenxin; Wang, Jianlong; Zhang, Lixue
Abstract : Facile and sensitive methyl parathion detection was achieved based on a novel carbon nanotube/carbon paper sensor. Abstract : This work developed an economic, convenient, sensitive and practical methyl parathion sensor using an easy-to-fabricate, reusable, inexpensive carbon nanotube/carbon paper composite as the working electrode. Carbon nanotubes form a network structure and provide large surface area, which can enhance the electron transfer capability of the carbon paper electrode. As an electrochemical sensing platform, the constructed carbon nanotube/carbon paper sensor allows sensitive determination of methyl parathion in the range of 10 ng mL −1 to 1000 ng mL −1 with a low detection limit of 3.9 ng mL −1 . Importantly, the present study demonstrated the high sensitivity, satisfactory stability and good anti-interference capabilities of this new electrode platform for methyl parathion detection. Furthermore, the present method was successfully applied to determine methyl parathion in kiwi samples with satisfactory precision (3.74–5.05%) of relative standard deviation (RSD) and acceptable recoveries (99.67–108%), which demonstrated the applicability of the carbon nanotube/carbon paper composite sensor. Such a facile approach for the detection of OPs may provide some guidance for designing nanomaterial-based sensors.